The nutrition and therapeutic potential of millets: an updated narrative review - Jacob, Jinu; Krishnan, Veda; Antony, Chris; Bhavyasri, Masimukka; Aruna, C.; Mishra, Kiran; Nepolean, Thirunavukkarasu; Satyavathi, Chellapilla Tara; Visarada, Kurella B. R. S. (Frontiers in Nutrition, 2024)
Millets are ancient small grains grown in arid and semiarid regions of the world. They are staple food for many people in Asia and Africa. They are abundant sources of minerals and vitamins, giving them the name Nutricereals. Moreover, millets contain valuable phytochemicals that impart therapeutic properties for various disorders and diseases, thus giving them nutraceutical value. A wide array of biochemical compounds are present in the plant parts as well as the grains. In the oldest texts of medicine in India and China, millets are mentioned for use for their medicinal value. There has been expanding interest and emerging facts about millets and their therapeutic uses. Ample evidence shows that consumption of millets amounts to correction of life style and metabolic disorders. Therapeutic properties of millets can be viewed in two ways, supplementary nutrition through minerals and vitamins, and therapeutic value through the presence of phytochemicals and specialty compounds that include flavonoids, phenolics, anthocyanidins and others that have antioxidant potential. Millets are gluten free, have low glycemic index and the phytochemicals aid in correction of lifestyle disorders and prevention of ailments like carcinogenesis. Supplementary benefits include treatment of anemia and calcium deficiency especially for pregnant women and young children. With the improvements in analytical methods for detection of various compounds, it is possible to identify the compound-specific genotypes in millets that can cater to the pharmacy industry. End-use specific genotypes can be bred to meet the demand. Millets being climate resilient, can contribute to a healthier life and better world through economic usage of natural resources.